No Child Left Behind? - Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
The title of this article is taken from the inspirational slogan of President George W. Bush, whose recently passed Elementary and Sunday Education Act bears this title. In this bill, as in the 1996 Welfare Reform Act, accountability won the day over federal fiscal support for low-income families. Of course, the 1996 Welfare Reform Act is a major 'accountability' success story, with the AFDC/TANF caseloads (households) falling from over 5.0 million in 1994 and 4.5 million in 1996 to 2.2 million cases by June 2000, about one third of the 6.6 million households which benefited from the SSI program in that same year. But, what is the larger context is within which we should interpret these programmatic changes and slogans? The slogan clearly challenges us to judge a society by how well it treats its children. But when we compare the well-being of American children Canadian or European kids, can we really say that the United States has not left any of its children behind? What can we say about equality of opportunity or fair life chances for America's children compared to their counterparts in other rich countries? This paper summarizes the poverty status of American children and then the variance in their 'real' standard of living. Then we briefly look at the reason why low-income American children and their parents are in such straits and conclude with a few low cost policy suggestions on how to improve the living standards of poor children, so that their greater accountability and better labor market for performance is rewarded by better family outcomes.
Keywords: 330; Kinder; Armut; Lebensstandard; USA